Location of the highest concentration of advection fogs on the Central Coast of Peru between the years 2000 -2014, using satellite images, as potential freshwater resources - León, Tatiana (2020)
The fogs form the vegetation of the Lomas, which are natural harvesters of fog water, the areas with the greatest vegetation, are the areas with the highest concentration of fog. An important characteristic in the Lomas is that altitude is the most important predictor of its plant richness, therefore to find the places with highest concentrations of fog, vegetation, and altitude are analyzed. The satellite data that give information on plant vigor and altitude of the Lomas are: the Normalized Vegetation Index (NDVI) and the Digital Elevation Model (DEM), with these data the vegetation of the Lomas, is located, then the correlation is analyzed between NDVI and altitude through topographic profiles that cross the most important Lomas of the coast. The results show that the NDVI increases with increasing altitude, reaching a maximum point from which the NDVI decreases as the altitude continues to increase, the higher the NDVI value, the greater the availability of water from the fog. Six Lomas distributed along the Central Coast of Peru were analyzed, resulting in that the maximum development of vegetation within a Loma is at an average height of 644.6 ± 101.8 masl, where it is the highest concentration of fog, a place where you can install fog catchers to collect water.